Perfomance enhancement of a fluidic oscillator - Furmidge, Neil (Cranfield University, 1996)
The operational performance criteria of fluidic oscillators are described in relation to the requirements of a domestic water meter. The problems associated with developing a novel water meter using fluidic oscillatory technology are discussed and the performance enhancements required to develop a fluidic oscillator capable of meeting the BS5728 (1979) domestic water meter specifications are presented. A sensingc onfigurationi s describedw hich providesa dequates ensitivityo ver the range required for a water meter with a nominal flowrate of one cubic meter per hour. The nozzled imensionsa re investigatedto reducet he pressured rop acrosst he fluidic water meter whilst still maintainingt he requiredt urndown rangea nd adequates ensitivity at low flowrates. The development of a novel fluidic oscillator flow conditioning device is described which radically improves the linearity of the fluidic oscillator and helps to reduce susceptibilityt o upstreamd isturbancesT. he device allows debris to passt hrough the meter without causing blockage and has an acceptable low pressure drop. Modificationst o the fluidic oscillatort ransducegr eometrya rei nvestigatedw hich reduce the minimum point of oscillation, thus increasing the turndown range of the water meter. Also geometry modifications are developed which improve the strength of the jet oscillation at low flowratesa nd therebys ignificantly increaseth e strengtho f signal. The effects of geometry modification on meter linearity and meterfactor response are investigated and a transducer design with enhanced range performance and improved linearity is described. Transducer designs are presented which are capable of meeting the BS5728 (1979) specification for both Class C and Class D QNLO domestic water meters.